Out of Place: Abandoned Children in Predicaments amid Alterations - Upadhyay, Prakash (Economic Literature, 2016)
The major argument of this article is that amid the rhetoric of inclusion of caste/ethnic/regional groups in the national mainstream, street children known as vagrant kids are the victims of exclusion. In a new situation on the streets, Vagrant kids are the vagabond. However, abandoning the home and adjusting to the streets is a multifarious process. The forming of the vagrant kids is a complex itinerary actions embedded with the age, sex, and ethnicities/caste, place of origin, family economy, family roles and responsibilities. Among the multiple factors, family dysfunctions and company with street boys are the raison d’être for the emergence of street children culture. In a transformed situation on street, kids’ lives have a momentous relationship to the street as a space and a new sub-culture in a new situation. In a rupture from works, which considers vagrant kids a hindrance to progressive social change, this study squabble that forming of vagrant kids is society ingrained and hence endorses role of community in bringing transference, meaningful development in the status of vagrant kids through an affirmative change in the behavior of the people and the government. Economic Literature Vol.12 2014: 26-38